An explicit investigation of occupational stress and safety behavior on the relationships between supportive leadership and safety compliance in sewerage industry - Ayu Suriawaty Bahkia; Zainudin Awang; Asad Rahman; Ayesha Nawal; Nor Azma Rahlin; Asyraf Afthanorhan (American Linguist Association, 2022)
This study aims to examine the influence of supportive leadership on occupational stress, safety behaviour and safety compliance of workers working in Indah Water Konsortium Sdn. Bhd. (IWK) Malaysia. Moreover, the study intends to investigate the mediational role of occupational stress and safety behaviour. Supportive leadership negatively influence occupational stress while positively influencing safety behaviour. Occupational stress put a negative effect on safety behaviour and safety compliance, while safety behaviour has a positive effect on safety compliance. Supportive leadership positively influences safety compliance. Occupational stress and safety behaviour partially mediate the relationship between supportive leadership and safety compliance. The outcomes of this study offer significant insights into the management of Indah Water Konsortium Sdn. Bhd. (IWK) to reduce occupational stress, encourage safety behaviour, and improve safety compliance by providing supportive leadership to the workers. Unlike other industries, the sewerage operation industry (in Malaysia) is under an intensive work burden and work pressure that eventually causes occupational stress, lack of safety compliance and ignorance of safety behaviours among workers. The link of supportive leadership with safety compliance is scared with the mediating role of occupational stress and safety behaviour, especially in the sewerage industry particularly in developing countries such as Malaysia.